Edukasi Penerapan Budaya Islam Jawa Pada Masyarakat Desa Watumas Di Masa Pandemi COVID-19 - Ma'rufah, Istinganatul; Albar, Mawi Khusni (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIN Prof. K.H. Saifuddin Zuhri, 2021)
This community service activity aims to educate the public about Islamic values by introducing Javanese Islamic art, namely hadroh while preserving Javanese culture with an Islamic spirit. Hadroh art is one of the most meaningful and enjoyable activities spreading and strengthening Islamic values. In Watumas Village, North Purwokerto District, Banyumas Regency, the activity was carried out. The method used in community service activities is online and offline methods. The online method is applied because there are still restrictions on community activities, while offline activities are in the form of hadroh art training, which requires face-to-face meetings. The activity participants were residents of Watumas Village by bringing in professional hadroh trainers. The activity results showed that there was high enthusiasm from the Watumas Village community inparticipating in the hadroh art training session.